Durable Membrane Electrode Assemblies for Proton Exchange Membrane Electrolyzer Systems Operating at High Current Densities. (20th August 2016) - Lettenmeier, P.; Wang, R.; Abouatallah, R.; Helmly, S.; Morawietz, T.; Hiesgen, R.; Kolb, S.; Burggraf, F.; Kallo, J.; Gago, A.S.; Friedrich, K.A.
Graphical abstract: Abstract: High efficiencies, wide operation range and rapid response time have motivated the recent interest in proton exchange membrane (PEM) electrolysis for hydrogen generation with surplus electricity. However, degradation at high current densities and the associated mechanism has not been thoroughly explored so far. In this work, membrane electrode assemblies (MEA) from different suppliers are aged in a commercial PEM electrolyzer (2.5 Nm 3 H2 h −1 ), operating up to 4 A cm −2 for more than 750 h. In all cases, the cell voltage (Ecell ) decreases during the testing period. Interestingly, the cells with Ir-black anodes exhibit the highest performance with the lowest precious metal loading (1 mg cm −2 ). Electrochemical impedance spectroscopy (EIS) shows a progressive decrease in the specific exchange current, while the ohmic resistance decreases when doubling the nominal current density. This effect translates into an enhancement of cell efficiency at high current densities. However, Ir concurrently leaches out and diffuses into the membrane. No decrease in membrane thickness is observed at the end of the tests. High current densities do not lead to lowering the performance of the PEM electrolyzer over time, although MEA components degrade, in particular the anode.